2015
DOI: 10.1007/s00395-015-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute DNase1 treatment improves left ventricular remodeling after myocardial infarction by disruption of free chromatin

Abstract: Myocardial infarction (MI) leads to necrosis and uncontrolled release of cellular content. Binucleated and polyploid cardiomyocytes contain high amounts of chromatin, a DNA polymer of histones which are cytotoxic. We hypothesized that chromatin from necrotic cells accumulates in the non-perfused, ischemic infarct region, causing local high concentrations of cytotoxic histones, thereby potentiating damage to the heart after MI. The endonuclease DNase1 is capable of dispersing extracellular chromatin through lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Histones released from necrotic cells accumulate within the myocardium early after myocardial infarction (MI), 55 inducing further dose-dependent myocardiocyte toxicity. NET-derived nucleosomes are also implicated in driving inflammatory signalling after cardiac ischaemia and are released via NETosis.…”
Section: Extracellular Histone In Acute Organ Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Histones released from necrotic cells accumulate within the myocardium early after myocardial infarction (MI), 55 inducing further dose-dependent myocardiocyte toxicity. NET-derived nucleosomes are also implicated in driving inflammatory signalling after cardiac ischaemia and are released via NETosis.…”
Section: Extracellular Histone In Acute Organ Injurymentioning
confidence: 99%
“…Targeting the release of histone complexes and, in particular, inhibiting NETosis has demonstrated considerable specificity and efficacy when used in animal models of AOI 55, 56, 60 and sepsis. 101 Specific PAD4 inhibitors prevent the citrullination of H3, a key step in releasing nucleosomic material for NET formation, 102 and are more effective than DNase1 in preventing tissue damage.…”
Section: Novel Approaches For Targeting Histonementioning
confidence: 99%
See 1 more Smart Citation
“…The attenuation of NA-induced tissue injury has also been attempted with DNase, RNase, small chemicals, and TLR inhibitors 7, 8, 26-31. These agents, however, have short serum half-lives, need to be administered frequently and at a high dose, and are costly.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, NETosis is the formation of extracellular traps from the nuclear release of neutrophils, resulting in the presence of histones in the extracellular space. Studies have shown that inhibiting or removing the PAD4 enzyme in various animal models led to increased survival (62,(86)(87)(88). The limitation of this treatment is the potential for off-target consequences of PAD4 disrupting the innate immune system (89).…”
Section: Current Therapeutics For Multiple Organ Dysfunction Caused Bmentioning
confidence: 99%